KERAGAMAN MAKANAN, ASUPAN MAKANAN DAN STATUS GIZI ANAK BALITA - Thresia Dewi Kartini; hendrayati Hendrayati; Suri Etika Yuniawati (Media Gizi Pangan, 2017)
Background: The diversity of food is one indicator of household food security level. The better the diversity of food, the better the quality of the nutritional intake of all family members, especially toddlers. The state of good nutrition and healthy in childhood become an important foundation for future health. The toddler has a rapid growth rate, and therefore the availability of nutrients to meet the needs for optimal child growth.Objective: This study aims to describe the diversity and food intake and nutritional status of children under five in Posyandu Bougenville 3 A Village Paccerakkang Makassar City.Mhetods: This study is a survey with descriptive approach. The research was conducted from January to July 2016. The sample was children aged 2-5 years were selected by purposive sampling as many as 33 people. Data about the diversity of food and nutrient intake were collected with food recall method 2 x 24 hours not consecutive. Weight anthropometric data of children under five were obtained by weighing using digital scales. Furthermore, the nutritional status of children under five is determined using WHO standards in 2005.Result: The research result shows that all samples are not diverse in eating food, less sample carbohydrate intake (69.7%), a good intake of protein samples (93.9%), fat intake less sample (75.8%), vitamin C intake less sample (97.0%), the intake of iron (Fe) less (60.6%), nutritional status of children under BB / U majority (69.7%) either.Sugesstion: It is advisable for parents, especially mothers in order to provide a variety of food (rice, meat of animal, vegetable side dishes, vegetables and fruit) in an amount sufficient so that all the nutrients needed by the body can be fulfilled.Keywords: The diversity of food, nutrient intake and nutritional status.